Sero‐prevalence and epidemiology of peste des petits ruminants in Libya. Issue 1 (12th July 2017) - Dayhum, A.; Sharif, M.; Eldaghayes, I.; Kammon, A.; Calistri, P.; Danzetta, M. L.; Di Sabatino, D.; Petrini, A.; Ferrari, G.; Grazioli, S.; Pezzoni, G.; Brocchi, E.
Summary: We conducted a cross‐sectional study during 2013 to quantify the serological prevalence of peste des petits ruminants( PPR) infection and to investigate host factors associated with PPR infection in small ruminants in Libya. A two‐stage sampling design was carried out. A total number of 148 flocks owning at least 100 heads each were randomly selected. Sixteen to forty‐eight samples were collected from each selected flock. A total number of 3, 508 serum samples from unvaccinated animals were collected and analysed at IZSLER Brescia, Italy, by using competitive ELISA, IDvet innovative diagnostics (IDvet 310, France). The overall serological prevalence among SR was 33% (95% CI: 31.4–34.5). Significant differences between the prevalence in the geographical branches were observed. The lowest prevalence level was observed in Zawiyah branch (16.1%), whereas the highest value was obtained for the Sabha branch (56.8%). Considering the age, a serological prevalence of 24.7%, 31.5% and 42.1% was observed in SR <1 year, between 1 and 2 years and more than 2 years, respectively. Statistically significant differences ( p < .001) in the sero‐prevalence levels were also observed between the age groups. Our findings suggest that the southern part of Libya could be more exposed to the infections coming from the neighbouring countries and this should be better investigated to correctly identify wherever specific entry points can be considered at higher risk than others. The results also confirmed the endemic status of PPR in Libya, with a constant exposure to the infection of the animals during their life. In the framework of the global strategy for control and eradication of PPR, our results, even if obtained by a preliminary study, can contribute to the assessment of the epidemiological situation of PPR in Libya as required by the Stage 1 of the plan.